Tracing COVID-19 Source of Infection Among Health Personnel in a Pediatric Hospital - de la Rosa-Zamboni, Daniela; Ortega-Riosvelasco, Fernando; González-García, Nadia; Gamiño-Arroyo, Ana Estela; Espinosa-González, Guillermo Alejandro; Valladares-Wagner, Juan Manuel; Saldívar-Flores, Araceli; Aguilar-Guzmán, Olivia; Sanchez-Pujol, Juan Carlos; López-Martínez, Briseida; Villa-Guillén, Mónica; Parra-Ortega, Israel; et al. (Frontiers in Pediatrics, 2022)
Health personnel (HP) have been universally recognized as especially susceptible to COVID-19. In Mexico, our home country, HP has one of the highest death rates from the disease. From the beginning of the SARS-CoV-2 pandemic, an office for initial attention for HP and a call center were established at a COVID-19 national reference pediatric hospital, aimed at early detection of COVID-19 cases and stopping local transmission. The detection and call center implementation and operation, and tracing methodology are described here. A total of 1,042 HP were evaluated, with 221 positive cases identified (7.7% of all HP currently working and 26% of the HP tested). Community contagion was most prevalent (46%), followed by other HP (27%), household (14%), and hospitalized patients (13%). Clusters and contact network analysis are discussed. This is one of the first reports that address the details of the implementation process of contact tracing in a pediatric hospital from the perspective of a hybrid hospital with COVID-19 and non-COVID-19 areas.